Variation in Soil Denitrification among Fertilization Regimes and Its Microbial Mechanism. Issue 8 (1st August 2022) - Wang, Haicui; Liu, Zhaodong; Li, Dandan; Ma, Lei; Zhao, Bingzi; Zhang, Jiabao
Abstract: A 27-year field experiment with various fertilization regimes was chosen for evaluating how fertilization regimes influence soil denitrification potential (SDP), to determine whether the microbial mechanism of SDP variation varies with fertilization regimes. The results showed that the compost (OM) fertilizer treatment presented the highest SDP followed by half compost plus half chemical fertilizer (NPKOM) treatment. Both SDPs were 3–25 times higher than those of the other treatments, and the SDP was higher in the OM than NPKOM, indicating an increase in SDP with the application of compost. The higher SDPs from OM and NPKOM were closely associated with higher abundances of functional genes, and enrichments of Rubrivivax gelatinosus and Azospirillum sp. TSO28-1, is mainly determined by the organic carbon (SOC), total nitrogen (TN), and dissolved organic carbon (DOC). For the treatments without compost, SDP mainly followed the order of chemical fertilizers of N and P (NP) > chemical fertilizers of N and K (NK) > unfertilized (Nil) > chemical fertilizers of N, P, and K (NPK) > chemical fertilizers of P and K (PK), in which the variations had a close association with different specific microbial species. That is, relative to Nil, the enhanced SDP in NP and NK was coupled with the enrichment of Ideonella sp. NC3L-43b and R. gelatinosus, likely due to their higher NO3 − contents, while the reduced SDP in NPK was linked to the depletions of R. gelatinosus and Azospira sp. NC3H-14, and that in PK to the depletion of R. gelatinosus and Azospirillum sp. TSO28-1, probably as a result of their lower N:P ratios. Microbial mechanisms for SDP differences varied with fertilization regimes, and R. gelatinosus can be regarded as a universal microbial indicator for SDP differences across the fertilization treatments.